Sol-gel synthesis and transmission of BaTiO3/SiO2 multilayer coatings - K. S. Sukalin; T. F. Raichenok; N. V. Gaponenko; K. V. Shaidakova; I. V. Lukonina; P. A. Kholov; I. V. Sveshnikov; K. R. Soma Raju (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
SOL-GEL METHOD, BARIUM TITANATE, FILTER.